Digging for (Ratings) Gold: The Connection Between Investigative Journalism and Audiences. (10th December 2019) - Abdenour, Jesse; Riffe, Daniel
ABSTRACT: Investigative journalism's value to democracy is straightforward: it provides useful information to citizens by exposing wrongdoing and holding powerful institutions accountable. But its financial value is questionable. There are indications that this often-expensive form of reporting can enhance audiences and thereby increase revenue, but very few large-scale projects have examined the connection between investigative content and audiences. Numerous studies have established a link between news quality and newspaper circulation, yet television studies of quality and audiences are less definitive. The present study addresses these research gaps, using Lacy's Model of News Demand to explain the interaction between investigative quality and U.S. local television audiences. Results show that investigative quality is strongly associated with larger television audiences, even when controlling for factors such as market competition and organizational structure. Investigative stories that disclosed concealed information were particularly predictive of audience size. However, stations producing a higher quantity of investigative stories were not associated with greater viewership. This suggests that investigative quality might be a more important audience motivator than quantity. The findings are discussed in light of the possibility that quality investigative journalism could provide economic as well as democratic benefits.